Iron Age in Augmented Reality - Nik Ahmad Fatihi Azmi; Suhazlan Suhaimi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The declining number of average grade subjects in History in Sijil Pelajaran Malaysia (SPM) among Malaysian students is an increasing concern in Malaysia. The purpose of this study is to investigate the connection between the factors that cause the students to become uninterested to study History and how they affect the number of average grades. This study also aims to provide a solution to help students become more interested in learning History. Using a cross-sectional analysis, this study analyzed the factors that cause students to lack interest to study History from 2016 – 2019. The lack of the ability to imagine the situation of historical events was found to play the greatest role in causing students to be less interested in learning History. This study definitively answers the question regarding correlation between the cause of lack of students’ interest in learning History and how it affects the number of average grade subjects.